A STUDY OF STATURE ESTIMATION FROM FACIAL ANTHROPOMETRIC MEASUREMENTS IN ADULT OF BHAVNAGAR REGION, GUJARAT - Desani A, Chauham; Modi, Nisarg Y (Journal of Forensic Medicine and Toxicology, 2019)
Background: Forensic anthropologists have devised number of measurements for describing the identity of men.. Stature is one of the primary identification data of an individual, hence occupies a unique position in medico legal cases and in the anthropological research areas. Material and Method: A cross sectional study was carried out on 427 males and 428 females belonging to the Bhavnagar region. The individuals of both the sexes aged between 18 years to 25 years were included in the study. The stature, Vertical facial length, Bigonial breadth of the individuals were measured. The stature was measured as vertical distance from vertex to the floor in mid-sagittal plane. Vertical facial length, Bigonial breadth were measured with the help of spreading caliper. Results & Conclusion: The statistical analysis showed the correlations between stature against Vertical facial length, Bigonial breadth measurements studied in males and females. The correlations were found to be statistically significant. The correlation coefficient was more between Vertical facial length and stature (0.271) than Bigonial breadth and stature (0.257) in males while in females correlation coefficient was more between Bigonial breadth and stature (0.232) than Vertical facial length and stature (0.153). The significant positive correlations between these two measurements and stature indicate that these variables can be successfully used to predict stature. Regression equations for stature estimation were calculated separately for males and females.
Keywords: Stature; Facial Anthroprometric measurement; Caliper; Correlation, Bhavnagar.